Neural correlates of fat preference in frontotemporal dementia: translating insights from the obesity literature. Issue 6 (11th May 2021) - Ahmed, Rebekah M.; Tse, Nga Yan; Chen, Yu; Henning, Elana; Hodges, John R.; Kiernan, Matthew C.; Irish, Muireann; Farooqi, I. Sadaf; Piguet, Olivier
Abstract: Objective: Alterations in eating behaviour are one of the diagnostic features of behavioural variant frontotemporal dementia (bvFTD). It is hypothesised that underlying brain network disturbances and atrophy to key structures may affect macronutrient preference in bvFTD. We aimed to establish whether a preference for dietary fat exists in bvFTD, its association with cognitive symptoms and the underlying neural mechanisms driving these changes. Methods: Using a test meal paradigm, adapted from the obesity literature, with variable fat content (low 20%, medium 40% and high 60%), preference for fat in 20 bvFTD was compared to 16 Alzheimer's disease (AD) and 13 control participants. MRI brain scans were analysed to determine the neural correlates of fat preference. Results: Behavioural variant FTD patients preferred the high‐fat meal compared to both AD ( U = 61.5; p = 0.001) and controls ( U = 41.5; p = 0.001), with 85% of bvFTD participants consistently rating the high‐fat content meal as their preferred option. This increased preference for the high‐fat meal was associated with total behavioural change (Cambridge Behavioural Inventory: rs = 0.462; p = 0.001), as well as overall functional decline (Frontotemporal Dementia Rating Scale: rs = −0.420; p = 0.03). A preference for high‐fat content in bvFTD was associated with atrophy in an extended brain network including frontopolar, anterior cingulate, insular cortices, putamen and amygdala extending into lateral temporal, posteromedial parietal and occipital cortices. Conclusions: Increased preference for fat content is associated with many of the canonical features of bvFTD. These findings offer new insights into markers of disease progression and pathogenesis, providing potential treatment targets.